Modernism and avant-garde: considerations on the distinction of concepts - Terekhovska, Olena (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2023)
The article discusses the difference between modernism and avant-garde as cultural-historical and philosophical-aesthetic phenomena.The aim of the article is to show the main discrepancy between modernism and avant-garde in terms of reception and their relationship to reality.The research method consists in the extrapolation of the evolutionary method (according to the classification of methods by V. M. Peretz) to the historical and literary situation of the 10-s and 20-s of the 20th century, in particular in the aspect of its consideration through the prism of the relationship and interaction of its iconic artistic and literary aesthetic phenomena of modernism and avant-garde. The evolutionary method involves the study of the natural development of phenomena, from their inception and through all stages of formation and development. Literature is considered in the dynamics of its historical development, taking into account cause-and-effect relationships between phenomena. Thus, the history of literature appears as an image of literary evolution on the basis of the general evolution of society and in connection with other separate evolutions that influenced it.In addition to evolutionary methods, the following methods were also used: systematic analysis, historical-genetic, comparative-comparative.The scientific novelty consists in an attempt to differentiate the concepts of modernism and avant-garde on the basis of their completely opposite reception and attitude to the contemporary reality, as well as in the analysis and systematization of already existing scientific positions on the specified problem.It has been proven that modernism, even in its mature phase, remained in opposition to real reality, focusing attention on the self-worth of man and art, while avant-garde, adopting its destructive energy, dynamism, militancy, technical audacity, transformed all this into its own aesthetic program. The absence of a harmonious relationship between man and nature, the dominance of material values over spiritual values, technocratization, militarism and rebellion, avant-garde turned into its cultural and artistic paradigm, making all this its philosophical and religious worldview. It has been found that avant-gardeism with all the variety of its currents is a multifaceted reflection of this contradictory revolutionary aggressive reality. Moreover, he is her creation, her pain and mouthpiece at the same time.Prospects for further research consist in the application of the evolutionary method in the analysis of poetic works of the era of mature modernism, with the aim of practical confirmation of the theoretical considerations proposed here.